Kegagalan Strategi Transnational Advocacy Network dalam Menentang Pengesahan Qanun Jinayat di Aceh - Jessica Aulia; Nurul Isnaini; R. Maisa Yudono (Universitas Airlangga, 2019)
This research paper frames the failure of contention against Islamic CriminalLaw (Qanun Jinayat) in Aceh as a strategic problem. In this research,the authors combine literature research and field observation in BandaAceh. Amidst the debate between the universalist and particularist pointof view regarding human right issues, local NGOs fighting against QanunJinayat have linked themselves with INGOs in a network of activists whichKeck and Sikkink (1998) refers to as Transnational Advocacy Network(TAN). It has undertaken multiple approaches aligned to the four typesof strategies as underlined by Keck and Sikkink (1998). However, suchstrategies are ineffective due to multiple features of the advocacy such ascomplexity of Indonesian law, difference in final objective of the elementsof TAN, and lack of strong representative figure as the front of the advocacy.In all, it can be concluded that although the pattern of transnationaladvocacy has emerged in Aceh, presence of such transnational networkhas not successfully advocated against the legalization of Qanun Jinayat.